Evaluation of the effects of sodium laurate on calcium carbonate precipitation: Characterization and optimization studies - POLAT, SEVGİ (ELSEVIER SCIENCE BV, 2019)
The effects of using sodium laurate as an additive on the calcium carbonate precipitation process and on the product characteristics were investigated experimentally through X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), particle size, and Brunauer, Emmett, and Teller (BET) analysis. The characterization results showed that the addition of sodium laurate to the crystallization media contributed to the formation of the vaterite form of calcium carbonate. The average particle size changed from 32 mu m to 14 mu m with increasing sodium laurate concentration. The SEM results suggested that the presence of sodium laurate had a strong influence on the calcium carbonate morphology and the crystals transformed from cubic to ellipsoidal shape. This study also emphasized the application of a statistical tool, response surface methodology (RSM) based on Box-Behnken design (BBD), to determine the optimal conditions for the production of calcium carbonate crystals with high specific surface area. The precipitation process was performed using different combinations of additive concentration, pH, and temperature, which are the main parameters affecting this process. The effects of these parameters on the responses, i.e., average particle size, surface area, and the relative fraction of vaterite, were investigated. Second-order polynomial equations were developed for the particle size, specific surface area and vaterite composition to correlate the parameters. The maximum specific surface area (12.430 mg/g) was obtained under the optimal conditions of 50 ppm additive concentration, pH 8.5, and 40 degrees C.
Keywords: Calcium carbonate; Crystallization; Experimental design; Sodium laurate; Vaterite; CRYSTALLIZATION; ULTRASONICATION; TRANSFORMATION; POLYMORPHS; ARAGONITE; DESIGN